Revision of the genus Conicera Meigen (Diptera, Phoridae) from China - Liu, Guang-Chun (Zootaxa, 2023)
The genus Conicera Meigen from China is revised. 35 species are recorded, of which 19 are new to science: C. obtusifinis sp. nov., C. petalina sp. nov., C. maculifemoris sp. nov., C. forcipis sp. nov., C. ancoraria sp. nov., C. angusta sp. nov., C. tortuosa sp. nov., C. dentisparsa sp. nov., C. convallis sp. nov., C. chayuensis sp. nov., C. triangularis sp. nov., C. margiflucta sp. nov., C. securiclata sp. nov., C. palmata sp. nov., C. marginata sp. nov., C. denticulata sp. nov., C. microspinulosa sp. nov., C. grandicaudata sp. nov. and C. obtusidentis sp. nov. 5 species are recorded for the first time in China: C. gracilis Michailovskaya, C. pacifica Michailovskaya, C. similis (Haliday), C. tibialis Schmitz and C. schnittmanni Schmitz. All known species are redescribed and illustrated. A key to species from China is presented.